Rancang Bangun Sistem Aplikasi ASBABUN Nuzul Berbasis Android dengan Metode Extreme Programming - Mud’is, Maulana Hasan; Khaerani, Izzah Faizah Siti Rusydati (Jurnal Algoritma, 2024)
The rapid development of technology has now become a major need in society, including in the system of practicing the Asbabun Nuzul worship series for those who believe in it. However, there is still a lot of Asbabun Nuzul data that has not been computerized, causing difficulties in collecting data and understanding Asbabun Nuzul in the Al-Qur'an. Therefore, an Asbabun Nuzul learning application which includes the works of Imam Suyuti and Al-Wahidi An-Nisaburi was developed to make it easier for people to read and understand Asbabun Nuzul per verse in the Al-Qur'an. This application was created using Android Studio with the Java programming language and has been tested using the blackbox method. This research was conducted by collecting data from literature studies and interviews. This application is intended for academics and reviewers who are interested in the field of the Al-Qur'an and Tafsir, it is hoped that it can help deepen understanding of the Al-Qur'an, provide a valid understanding of the verse, and avoid difficulties in understanding the meaning and purpose of the verse.